Penerapan Pendekatan Deep Learning di Pembelajaran Intrakurikuler dan Kokurikuler pada Jenjang Sekolah Menengah Pertama - Senowarsito; Soedjono; Yuli Kurniati Werdiningsih; Ale Sandya Rindi Amida (Jurnal Ilmiah Pengabdian dan Inovasi, 2026)
The current national education system uses two main frameworks that are still flexible, namely the Independent Curriculum and the 2013 curriculum. The purpose of this activity is to provide understanding and training on deep learning approaches in intracurricular and co-curricular learning. The main focus in this curriculum is deep learning. Through initial studies and observations at partner schools, the initial conditions of mentoring, or current priority problems experienced by the first partner, there are still teachers who do not understand the principles of deep learning. Second, there has been no development of deep learning-based teaching tools. Third, there are still teachers who have not implemented active learning methods. Fourth, there has been no implementation in the official curriculum. Based on the initial conditions of mentoring or priority problems experienced by the partners, the solution offered by the first service team is to socialize teachers about the principles of the deep learning approach in learning. Second, the service team helps teachers develop deep learning-based teaching tools. Third, the service team conducts active learning method training using renewable technologies. Fourth, the service team provides assistance in the implementation of the official curriculum. The methods used in this PKM include socialization, training, mentoring, monitoring, evaluation, and follow-up. The service team contributes as facilitators, trainers, and companions who help teachers transition from theoretical understanding of deep learning to real-world practice in the classroom, while ensuring its sustainability through school policy support. This activity has achieved its goal, which is to successfully overcome the problems experienced by partners.